2007
DOI: 10.1524/ract.2007.95.7.409
|View full text |Cite
|
Sign up to set email alerts
|

Modeling batch kinetics of cesium, cobalt and strontium ions adsorption from aqueous solutions using hydrous titanium oxide

Abstract: Hydrous titanium oxide was chemically synthesized and tested as adsorbent material for the removal of cesium, cobalt and strontium ions from chloride waste solutions using batch technique. The influences of pH, contact time, and temperature have been reported. The uptake of both strontium and cobalt ions was found to be greater than that of cesium and the apparent sorption capacity of each ion increases with increase in temperature. Thermodynamic parameters such as changes in Gibbs free energy (Δ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The mechanistic homogeneous particle diffusion model (HPDM) [29,32], was attempted following the method presented by Metwally et al [29] (Fig. S7).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanistic homogeneous particle diffusion model (HPDM) [29,32], was attempted following the method presented by Metwally et al [29] (Fig. S7).…”
Section: Methodsmentioning
confidence: 99%
“…Rates of cation-exchange can be calculated by using different kinetic models as pseudo-first-order or pseudo-second-order rate models [29]. In the case of LTA powders and LTA-monolith M0 (featuring no mesoporosity), it has already been shown that a pseudo second-order model describes accurately the kinetics of cation adsorption [9].…”
Section: Strontium Adsorption Kinetics In Batch Modementioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, the presence of two linear zones in these plots can be explained by two sorption processes: external mass transfer, such as boundary-layer diffusion, and intra-particle diffusion. The initial curve zone is attributed to the external diffusion, and the second linear zone is defined as the intra-particle diffusion (Crini et al 2007;Metwally et al 2007). Moreover, the slope of this second linear zone can be considered the intradiffusion coefficient.…”
Section: Adsorption Kineticsmentioning
confidence: 99%